CHANGING LEGAL PLURALISM IN INDONESIA - Franz Von Benda Beckmann (Yuridika, 2017)
The way out of the theoretical impasses of conventional legal sociology and anthropology leads into the "jungle of legal pluralism" (F.von Benda-Beckmann 1983a)Please download this full article